2009
DOI: 10.1002/cjg2.1402
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Africa Magnetic Anomaly in Controlling the Magnetic Configuration and its Secular Variation

Abstract: The configuration of the Earth's main magnetic field and its secular variation are greatly controlled by the nondipole field. This portion of the main field exhibits as 5 planetary-scale magnetic anomalies in Australia, Africa, Eurasia, North America, and South Atlantic Ocean, as well as a few minor anomalies. Only anomaly in the equatorial region is the Africa anomaly, which affects seriously the shape and position of the magnetic equator, pushing the equator northward for 15• at maximum. The fast westward dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Ion PERs with large negative amplitudes, for example, A < −100%, were successfully detected predominantly in winter during the night in most mentioned magnetic anomalies of the world, like the Africa anomaly and SAMA (Figure 7). Xu and Bai [57] concluded that these planetary-scale non-dipole fields could heavily control the secular variation in geomagnetic fields, and the combined effect from the Africa anomaly and SAMA have tremendously modified the shape and position of the magnetic equator. Unexpectedly, we also found a large negative ion density anomaly from Southeast China to the Japanese Ocean (Figure 7), but its formation mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion PERs with large negative amplitudes, for example, A < −100%, were successfully detected predominantly in winter during the night in most mentioned magnetic anomalies of the world, like the Africa anomaly and SAMA (Figure 7). Xu and Bai [57] concluded that these planetary-scale non-dipole fields could heavily control the secular variation in geomagnetic fields, and the combined effect from the Africa anomaly and SAMA have tremendously modified the shape and position of the magnetic equator. Unexpectedly, we also found a large negative ion density anomaly from Southeast China to the Japanese Ocean (Figure 7), but its formation mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The key point is that these PERs are of similar space size at ~100 s, 700 km, if a velocity of the DEMETER satellite of 7 km/s is considered, possibly illustrating the outcome of the satellite flying over the same region at different times. Xu et al [57] reported that there are mainly five planetary-scale geomagnetic anomalies worldwide: Australia, Africa, the Southern Atlantic Ocean, the Eurasian continent, and Northern America. However, in these areas, a strong We examined all night PERs and found that there are 196 with an amplitude less than −100% in total, and they occurred mostly in equinox and winter, with a few occurring in summer.…”
Section: Seasonal Variation In Ionospheric Persmentioning
confidence: 99%
“…It is well known that the geomagnetic non-dipole field zones are five large-scale anomalies (Xu & Bai, 2009), which are listed according to their maximum intensities as follows: the South Atlantic Ocean anomaly (SAA), Africa anomaly (AFR), Eurasia anomaly (ERA), Australia anomaly (AST), and North America anomaly (NAM).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the geomagnetic non‐dipole field zones are five large‐scale anomalies (Xu & Bai, 2009), which are listed according to their maximum intensities as follows: the South Atlantic Ocean anomaly (SAA), Africa anomaly (AFR), Eurasia anomaly (ERA), Australia anomaly (AST), and North America anomaly (NAM). In particular, the two strongest negative anomalies (defined in total intensity) SAA and AFR dramatically distort the morphology of the geomagnetic field in the African sector, as shown in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…The key point is that these PERs are of the similar space size of ~100 s, 700 km if velocity of the DEMETER satellite 7 km/s is considered, maybe rightly illustrating the outcome of the satellite flying over the same region at different time. Xu et al [56] have reported that there are mainly five planetary scale geomagnetic anomalies worldwide: Australia, Africa, Southern Atlantic Ocean, Eurasia continent and Northern America. However, in these areas, strong negative ionospheric anomaly has not been detected in Northern America but in eastern Asia including southeast China and Japan in this time.…”
Section: Seasonal Variation Of Ionospheric Persmentioning
confidence: 99%